Thickness of orthodontic clear aligners after thermoforming and after 10 days of intraoral exposure: a prospective clinical study - Rosaria Bucci; Roberto Rongo; Carmine Levatè; Ambrosina Michelotti; Sandro Barone; Armando Viviano Razionale; Vincenzo D'Antò (SpringerOpen, 2019)
Abstract Background Clear aligners (CA) are among the most chosen orthodontic therapies for patients who require an invisible treatment. Previous studies showed that the thermoforming process and the complexity of the intraoral environment might alter the properties of these devices. The aim of the current prospective clinical study was to assess the thickness changes of the CA after 10 days of intraoral use. The secondary aim was to assess the reproducibility of the thermoforming process, in terms of aligner thickness. Materials and methods CA from 18 consecutive patients (13 women, 5 men, mean age 28.8 ± 9.6 years) were investigated. Before intraoral exposure (T0), the thickness of the unused CA was measured at different occlusal points on a 3D model with a dedicated software (Geomagic Qualify 2013; 3D Systems, Rock Hill, SC, USA). Two CA configurations were studied: passive maxillary aligner (P-no tooth movement; no shape for attachments) and active maxillary aligner (A-tooth movement; shape for attachments and divot). The used aligners were returned after 10 days (T1) and the thickness measurements were repeated. A Student's t test for paired data (T1 vs. T0) was applied to compare the thicknesses of used and unused devices (significance level after Bonferroni correction for multiple comparison was set at p < 0.0014). Furthermore, to study the reproducibility of the thermoforming process, P and A aligners were thermoformed twice, and the thicknesses of the two unused thermoformed devices were compared by means of Student's t test for paired data (significance level after Bonferroni correction for multiple comparison was set at p < 0.0014) and Dahlberg's error. Results The thermoforming process showed good reproducibility for both aligner configurations, with a maximum Dahlberg's error of 0.13 mm. After intraoral use, the thickness of P showed some statistically significant, but not clinically relevant, thickness changes as compared to the unused aligners, while A did not show any significant changes. Conclusion Considering the thickness changes, the thermoforming process is reliable both with active and passive aligner configurations. Also, the CA examined show good thickness stability after physiological intraoral ageing in a population of healthy adults.